Rapid Generation of Barley Mutant Lines With High Nitrogen Uptake Efficiency by Microspore Mutagenesis and Field Screening - Gao, Runhong; Guo, Guimei; Fang, Chunyan; Huang, Saihua; Chen, Jianmin; Lu, Ruiju; Huang, Jianhua; Fan, Xiaorong; Liu, Chenghong (Frontiers in Plant Science, 2018)
In vitro mutagenesis via isolated microspore culture provides an efficient way to produce numerous double haploid (DH) lines with mutation introduction and homozygosity stabilization, which can be used for screening directly. In this study, 356 DH lines were produced from the malt barley (Hordeum vulgare L.) cultivar Hua-30 via microspore mutagenic treatment with ethyl methane sulfonate or pingyangmycin during in vitro culture. The lines were subjected to field screening under high nitrogen (HN) and low nitrogen (LN) conditions, and the number of productive tillers was used as the main screening index. Five mutant lines (A1-28, A1-84, A1-226, A16-11, and A9-29) with high numbers of productive tillers were obtained over three consecutive years of screening. In the fifth year, components related to N-use efficiency (NUE), including N accumulation, utilization, and translocation, were characterized for these lines based on N uptake efficiency (NUpE), N utilization efficiency (NUtE), and N translocation efficiency (NTE). The results show that the NUpE of four mutant lines (A1-84, A1-226, A9-29, and A16-11) improved significantly under HN, whereas that of two lines (A1-84 and A9-29) improved under LN. As a result, their NUE improved greatly. No improvement in NUtE was observed in any of the five mutant lines. A1-84 and A9-29 were selected as an enhanced genotype in N uptake, and A1-28 showed improved NTE at the grain-filling stage. Our results imply that high-NUpE mutants can be produced through microspore mutagenesis and field screening, and that improvement of NUE in barley depends on enhancement of N uptake.